Efficient hydrogen peroxide reduction in glutathione peroxidase cycle using cost-effective FeSe2 nanospheres - Khan, Saif; Bhagwath, Sundeep S.; Ajmal, Mohammad Rehan; Ansari, Intikhab A.; Lohani, Mohtashim; Raghunandana, Sanjaya Pavgada; Luqman, Mohammad (Frontiers in Agronomy, 2025)
IntroductionHydrogen peroxide plays a crucial role in melanogenesis by regulating tyrosinase activity, the key melanin-forming enzyme responsible for the browning of fruits, vegetables, and seafood. The need for effective solutions to mitigate such browning processes highlights the significance of developing advanced catalytic agents.MethodsWe synthesized highly effective FeSe2 nanospheres using a one-step solvothermal process. The nanospheres were characterized through transmission electron microscopy (TEM), energy-dispersive X-ray analysis (EDX), and powder X-ray diffraction (XRD). Enzymatic activity was evaluated by plotting Michaelis-Menten and Lineweaver-Burk graphs to calculate the Vmax and Km parameters. Comparative analyses with a control sample and other known enzymes were performed to assess the catalytic efficiency.Results and discussionFeSe2 nanospheres successfully catalyzed the reduction of hydrogen peroxide to water and alcohol, demonstrating enzyme-like activity. The initial reaction rate was 11 times higher than the control sample and significantly outperformed other enzymes, except for those relying on expensive noble metals. These nanospheres (termed Nanozymes) mimic the enzymatic action of natural antioxidants, such as the glutathione peroxidase (GPx) enzyme, in biological systems. Their exceptional efficiency makes them a strong candidate for practical applications in mitigating early browning caused by melanogenesis.ConclusionsFeSe2 nanozymes exhibit great promise as a biocatalyst for enhancing the shelf life of fruits and vegetables by reducing damage due to early melanogenesis. This cost-effective and efficient alternative to natural or noble metal-based enzymes offers significant potential for applications in food preservation and other industries.